2023
DOI: 10.29333/iji.2023.16150a
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Literacy Workshop to Improve Reading Ability of Elementary School Students

Abstract: Elementary school students in the Siosar shelter area experienced trauma and lagging behind learning, especially reading as effect of the Mount Sinabung disaster which often erupts. This action research is to improve the quality of reading learning for elementary school students affected by the Mount Sinabung disaster in the Siosar shelter area, Indonesia. Reading problems experienced by students include difficulty recognizing letters, spelling stammering, difficulty reading words, not paying attention to punc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…For example, some of these issues are the websites' reliability, having information about citation and bibliography to prevent plagiarism, and knowing the features of programs that teach writing. Similarly, Halimatussakdiah and Sumarwati, (2021) found that audiovisual media has positive effects on writing skills. Using media to develop writing provides a more enjoyable learning environment for the student as it contains both audio and visual elements.…”
Section: Using Technological Devices In Teaching Writingmentioning
confidence: 93%
“…For example, some of these issues are the websites' reliability, having information about citation and bibliography to prevent plagiarism, and knowing the features of programs that teach writing. Similarly, Halimatussakdiah and Sumarwati, (2021) found that audiovisual media has positive effects on writing skills. Using media to develop writing provides a more enjoyable learning environment for the student as it contains both audio and visual elements.…”
Section: Using Technological Devices In Teaching Writingmentioning
confidence: 93%
“…Kendala dalam kemampuan membaca yang rendah dan kurangnya motivasi belajar siswa saat ini membutuhkan metode, sumber pembelajaran membaca yang dapat menstimulus semangat belajar siswa (Fauziah et al, 2023). Pembelajaran harus terjadi dalam lingkungan yang santai, nyaman, dan menghibur dibanding dengan kegiatan pembelajaran secara formal yang sering kali membuat siswa merasa jenuh (Halimatussakdiah et al, 2023).…”
Section: Pendahuluanunclassified
“…Penelitian terdahulu yang diakukan oleh Riana & Abadi (2022) hasil pembelajaran bagi siswa di kelas pendidikan umum (Halimussakdiah et al, 2023). Anafiah (2018) mengemukakan bahwa permainan yang memperkaya keterampilan literasi dapat meningkatkan pengetahuan dan kemampuan anak tentang fungsi bahasa tulis, menulis, dan menggunakan strategi pemahaman seperti mengidentifikasi dan mengoreksi tulisan sendiri.…”
Section: Pendahuluanunclassified